Correlation Between Neck Pain And Visual Disturbances In Smartphone Users - Yasmin Saeed Mohamed Ibrahim Atallah; Mohamed Hussein Elgendy; Heba Mohamed Farag Elfeky (2024)
Neck pain is a major concern among today's most common health conditions, which may affect quality of life. Many people with neck pain complain of visual disturbances, which also affect their lives and reduce visual performance. Objective: The current study was carried out to Investigate and examine the relationship between neck pain and visual disturbances in smartphone users
(3BdGe GdQbHI gj eUOQ bdb cHjQ Hjf GdMGdGJ GdUMjI GdCcKQ TjhYG Gdjhe(B. (3hgj JMJd GdeQJHI GdQGHYI YGdejkG ef MjK GdEYGbI GdJj bO JDKQ Ydi LhOI GdMjGI(B. (3MjK jTch GdcKjQ ef GdCTNGU GdPjf jYGfhf ef BdGe GdQbHI ef GVWQGHGJ HUQjI, hGdJj JDKQ CjkVG Ydi MjGJge hJbdd ef GdCOGA GdHUQj(B. (3GdgOa ef gPg GdQSGdI (B: (3CLQjJ GdOQGSI GdMGdjI dHMK hOQGSI GdYdGbI Hjf BdGe GdQbHI hGdGVWQGHGJ GdHUQjI dOi eSJNOej GdgGJa GdPcj(B.s
Thesis (M.Sc.) -Cairo University, 2024.
Bibliography: pages 71-86.
Issued also as CD
Text in English and abstract in Arabic & English.
Keywords: Physical Therapy; Chronic ankle instability -- Wii fit rehabilitation training -- Conventional physical therapy program; (3BdGe GdQbHIs -- (3GdGVWQGHGJ GdHUQjIs -- (3GdgGJa GdPcjs